2015
DOI: 10.1182/blood.v126.23.323.323
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of AG-221, a Potent Inhibitor of Mutant IDH2 That Promotes Differentiation of Myeloid Cells in Patients with Advanced Hematologic Malignancies: Results of a Phase 1/2 Trial

Abstract: Background: There is an unmet need fortreatments (Tx) for myeloid malignancies, particularly relapsed/refractory (RR) AML, that provide durable remissions without worsening existing cytopenias that place patients (pts) at risk for serious infections or bleeding. Oral AG-221 is a selective, potent inhibitor of the mutant isocitrate dehydrogenase 2 (mIDH2) enzyme associated with hematologic malignancies. A phase 1/2 dose-escalation and expansion study of AG-221 [NCT01915498] is ongoing in pts with advanced hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…32 In a phase 1/2 study of the IDH2 mutant inhibitor enasidenib for the treatment of patients with IDH2 mutation-positive advanced hematologic malignancies (particularly acute myeloid leukemia), the overall response rate was 41% among 198 IDH2mutated acute myeloid leukemia patients, and the complete remission rate was 17%. 33 In another clinical trial of enasidenib treating 17 myelodysplastic syndrome patients with IDH2 mutations, the overall response rate was 59%. 34 In addition, am IDH2 mutation may predict sensitivity to DNA methyltransferase inhibitors such as the Food and Drug Administration-approved therapies azacitidine and decitabine.…”
Section: Discussionmentioning
confidence: 99%
“…32 In a phase 1/2 study of the IDH2 mutant inhibitor enasidenib for the treatment of patients with IDH2 mutation-positive advanced hematologic malignancies (particularly acute myeloid leukemia), the overall response rate was 41% among 198 IDH2mutated acute myeloid leukemia patients, and the complete remission rate was 17%. 33 In another clinical trial of enasidenib treating 17 myelodysplastic syndrome patients with IDH2 mutations, the overall response rate was 59%. 34 In addition, am IDH2 mutation may predict sensitivity to DNA methyltransferase inhibitors such as the Food and Drug Administration-approved therapies azacitidine and decitabine.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of response was 6Á9 months (Stein et al, 2015). Similarly, a phase I study of the IDH1 inhibitor AG-120 demonstrated an overall response rate of 35% (DiNardo et al, 2015). Accrual has started on a phase I study exploring the safety of combining AG-120 and AG-221 with both induction and consolidation chemotherapy and with 5azacitidine (NCT02632708 and NCT0267792).…”
Section: Isocitrate Dehydrogenase (Idh) Mutationsmentioning
confidence: 99%
“…Preliminary evidence presented at the last ASH meeting reported the results of the ongoing phase I/II clinical studies in patients with hematologic malignancies, reporting promising results. There was a marked decline of 2-HG levels in patients with both R140Q and R172-mutated IDH2 protein, a complete remission rate of 21.7% among relapsed/refractory AML, and a significant proportion of patients with a durable partial response or stable disease showing a restoration of normal hematopoiesis [155,156]. These results are promising because the majority of the treated patients were relapsed/refractory.…”
Section: Idh Mutationsmentioning
confidence: 99%